Local governments and forests in the Bolivian lowlands - Kaimowitz, D.; Pacheco, P.; Johnson, J.; Pavez, I.; Vallejo, C.; Velez, R. (Overseas Development Institute, 1999)
This paper evaluates Bolivian's recent experience of giving municipal government a role in forest management. It first provides background information on Bolivia's decentralisation policies, including the 1994 Popular Participatiion Law and the 1996 forestry law. It then presents case studies of four specific municipalities: Ascencion de Guarayos, Rurrenabaque, Villa Tunari, and San Ignacio de Velasco. It concludes that decentralisation has created new opportunities for marginal groups, but they have not always been able to take advantage of those opportunities. Municipal forest reserves could provide small-scale loggers with greater access to forest resources, yet institutional, technical, and organisational constraints impede their full implementation. Local government municipalities are interested in forest issues but their capacity to address them remains limited. While they show sign of interest in sustainable forest management, they are unlikely in the short term to make major progress on reducing deforestation, regulating concession management, or improving small timber management